Synthetization of TiC surface hardening using TIG melting technique - The effect of working distance. Issue 1 (1st June 2022) - Idriss, A. N. Md; Maleque, M. A.; Afiq, A
Abstract: Surface hardening with and without hard reinforcing material can be achieved by melting technique on the top substrate area via high energy input fusion. The aim is to apply TIG torch heat input of 1344 J/mm at two different working distances such as 0.5 mm and 1.5 mm to incorporate the preplaced TiC particulates on the surface of AISI 4340 low alloy steel. Results pertaining to the microstructural features, melt pool sizes, defects, topographies and microhardness were investigated using the optical microscope, scanning electron microscope and Vickers microhardness tester. The results showed that the heat loss through the arc column at 1.5 mm of working distance resulted small melt pool geometry and poor dissolution of TiC particulates. Lower working distance increases heating value leading more precipitation of TiC whilst minimizing those the undissolved particulates. The surface submerged at working distance of 0.5 mm produced microhardness ranging from 800 HV to 1500 HV. The work suggested that heat fusion can be enhanced by marginal working distance whilst saving the energy to melt instead of increasing the used voltage, current, decreasing scanning speed, or adding fluxes or shielding with special gasses.